Leadership lessons from the Cherokee Nation learn from all I observe - Smith, Chadwick Corntassel (McGraw Hill, 2013)
In Leadership Lessons from the Cherokee Nation, Smith combines Cherokee wisdom handed down from generation to generation with a smart leadership approach that takes today's very real issues into consideration. He explains why this leadership approach works and how you can apply it to your own organization, whether business, government, or nonprofit. Learn all the lessons that drive powerful leadership, including how to: - Be a lifelong learner - Solve problems with creativity and innovation - Recruit and develop strong leaders - Delegate wisely - Act with integrity and dignity - Don't be distracted from your objective - Lead by example